2022
DOI: 10.1038/s43018-022-00431-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ectopic JAK–STAT activation enables the transition to a stem-like and multilineage state conferring AR-targeted therapy resistance

Abstract: Emerging evidence indicates that various cancers can gain resistance to targeted therapies by acquiring lineage plasticity. Although various genomic and transcriptomic aberrations correlate with lineage plasticity, the molecular mechanisms enabling the acquisition of lineage plasticity have not been fully elucidated. We reveal that Janus kinase (JAK)–signal transducer and activator of transcription (STAT) signaling is a crucial executor in promoting lineage plasticity-driven androgen receptor (AR)-targeted the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 82 publications
4
100
0
Order By: Relevance
“…As JAKs/STATS are activated by both IFN and OSM/IL6 receptors, it is conceivable that OSM/IL6 only activates a subset of the IFN-induced genes with tumor-promoting activity, as the case for Mx1 75 . Consistent with our findings, JAK/STAT signaling has recently been shown to initiate the lineage plasticity in prostate cancer as well as to promote lineage plasticity-driven targeted therapy resistance in a stem-like subpopulation of prostate cancer 76,77 . On the other hand, Aouad et al showed that epithelial-mesenchymal plasticity is essential for the generation of a dormant cell state of ER + breast cancer during progression, and the activation of IL6-JAK-STAT signaling triggers tumor cell awakening and recurrence 48 .…”
Section: Discussion (1470 Words -> 1689 Now … Omg)supporting
confidence: 91%
“…As JAKs/STATS are activated by both IFN and OSM/IL6 receptors, it is conceivable that OSM/IL6 only activates a subset of the IFN-induced genes with tumor-promoting activity, as the case for Mx1 75 . Consistent with our findings, JAK/STAT signaling has recently been shown to initiate the lineage plasticity in prostate cancer as well as to promote lineage plasticity-driven targeted therapy resistance in a stem-like subpopulation of prostate cancer 76,77 . On the other hand, Aouad et al showed that epithelial-mesenchymal plasticity is essential for the generation of a dormant cell state of ER + breast cancer during progression, and the activation of IL6-JAK-STAT signaling triggers tumor cell awakening and recurrence 48 .…”
Section: Discussion (1470 Words -> 1689 Now … Omg)supporting
confidence: 91%
“…IBC is relatively resistant to therapies, which may be due to the high frequency of stem cell–like cells with activated JAK/STAT3 signaling ( 59, 60 ). In prostate cancer, JAK2/STAT3 activation led to lineage plasticity, whereby switching from a luminal androgen receptor positive phenotype to mesenchymal/neuroendocrine state was associated with resistance to anti-androgens and metastatic progression ( 61, 62 ). We also observed substantial differentiation state-related heterogeneity within our IBC cell lines and treatment with paclitaxel and the development of resistance increased the relative frequencies of EpCAM low VIM high CD44 high CD24 low pSTAT3 + cells in TN-IBC lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the identification of histone deacetylases and other epigenetic modifying agents is consistent with the known importance of epigenetic regulation of androgen receptor signaling [60, 61]. Other targets, however, are linked to AR signaling bypass, as in the case of PTEN loss and subsequent constitutive activation of PI3K signaling [62], activation of JAK/STAT and FGFR signaling during the acquisition of AR independence and lineage plasticity [63, 64], and the role of Syk as a potential mediator of invasive features and bone metastasis [65]. While the relevance of these targets is well supported by preclinical evidence, the clinical utility of these targets is more varied.…”
Section: Discussionmentioning
confidence: 85%